Interleukin-1 receptor antagonist, mode of analgesia and risk of Caesarean delivery after onset of labour: a Mendelian randomisation analysis. (January 2022) - Ackland, Gareth L.; Van Duijvenboden, Stefan; Abbott, Tom E.F.; Gutierrez del Arroyo, Ana; Wilson, Matthew J.; David, Anna L.; ,; Ali, Amaan; Wikner, Matt; Noblett, James; Usman, Nusrat; Wray, Sarah; et al.
Abstract: Background: Lower circulating levels of the anti-inflammatory cytokine interleukin-1 receptor antagonist (IL-1ra) are associated with intrapartum inflammation and epidural analgesia-related maternal fever, both of which increase the rate of obstetric interventions. We hypothesised that genetic variants determining IL-1ra levels would be associated with Caesarean delivery rates after the onset of labour. Methods: We performed Mendelian randomisation analyses in parous women ≥16 yr old who received either non-neuraxial or neuraxial analgesia for their first two labours (UK Biobank). We used an established genetic score (calculated as 0–4, determined by the presence/absence of rs6743376 and rs1542176 alleles), in which the complete absence of both alleles causes the lowest IL-1ra levels. The primary outcome was Caesarean delivery after the onset of labour (odds ratio [OR]: 95% confidence intervals). Results: There were 7731 women (mean [standard deviation] age at first birth: 25 [5] yr) who had complete genetic scores and delivery data. For women who received non-neuraxial analgesia, Caesarean delivery rates were different across allele scores (χ 2 =12.4; P =0.015): 104/596 (17.4%) women with zero allele score underwent Caesarean delivery, compared with 654/5015 (13.0%) with allele score ≥1 (OR 1.41; 1.12–1.77). For women who had neuraxial analgesia, Caesarean delivery was not different across allele scores, ranging from 18.1% to 20.8% (χ 2 =0.29; P =0.99). Caesarean delivery was independent of type of analgesia for 818/7731 (10.6%) women with zero allele scores (OR 0.93; 0.63–1.39), but was higher in women receiving neuraxial analgesia with allele scores ≥1 (OR 1.55; 1.35–1.79; P <0.001). Conclusions: Mendelian randomisation analysis suggests that higher IL-1ra levels are associated with reduced Caesarean delivery rate. Neuraxial analgesia appears to disrupt this link. Clinical trial registration: UK Biobank study 62745.